2005
DOI: 10.1007/s00221-004-2137-1
|View full text |Cite
|
Sign up to set email alerts
|

Joint angle variability in 3D bimanual pointing: uncontrolled manifold analysis

Abstract: The structure of joint angle variability and its changes with practice were investigated using the uncontrolled manifold (UCM) computational approach. Subjects performed fast and accurate bimanual pointing movements in 3D space, trying to match the tip of a pointer, held in the right hand, with the tip of one of three different targets, held in the left hand during a pre-test, several practice sessions and a post-test. The prediction of the UCM approach about the structuring of joint angle variance for selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 29 publications
8
75
1
1
Order By: Relevance
“…These studies have shown that indices of synergies can increase with practice (Kang et al 2004;Latash et al 2003), or decrease (Domkin et al 2002), or stay unchanged (Domkin et al 2005). A conclusion has been drawn that early stages of practice of a novel task are characterized by emergence and strengthening of synergies stabilizing important performance variables.…”
Section: Effects Of Practice On Modes and Synergiesmentioning
confidence: 99%
“…These studies have shown that indices of synergies can increase with practice (Kang et al 2004;Latash et al 2003), or decrease (Domkin et al 2002), or stay unchanged (Domkin et al 2005). A conclusion has been drawn that early stages of practice of a novel task are characterized by emergence and strengthening of synergies stabilizing important performance variables.…”
Section: Effects Of Practice On Modes and Synergiesmentioning
confidence: 99%
“…During two-arm pointing, the joints within each arm have been shown to stabilize the trajectory of the endpoint while across two-arms the vectorial distance between the endpoints was stabilized (Domkin et al 2002(Domkin et al , 2005.…”
Section: Hierarchies Of Synergies In Natural Movementsmentioning
confidence: 99%
“…However, in all the cited studies of prehension, the subjects received no feedback on the action of the VF; nevertheless, its action was stabilized by combined action of the four fingers. During pointing tasks, the subject's attention was drawn to relative motion of the two hands; nevertheless, multi-joint synergies stabilized each hand's trajectory were seen (Domkin et al 2002(Domkin et al , 2005. Similarly, during postural tasks, multi-muscle analysis revealed the presence of synergies stabilizing shifts of the center of pressure (COP, the point of application of the resultant force acting on the body from the support surface) despite the fact that no feedback was available on the COP shifts (Krishnamoorthy et al 2003;Wang et al 2005).…”
Section: Hierarchies Of Synergies In Natural Movementsmentioning
confidence: 99%
“…A relatively common thread of those studies which used the UCM approach to address changes in movement coordination has been a decrease in both components of variance with learning (Domkin et al 2005(Domkin et al ,2002Yang and Scholz 2005). Depending on the study, the decrease in V UCM could be smaller than , equal to (Domkin et al 2005) or greater than (Domkin et al 2002) the decrease in V ORT . Based on the results of learning a challenging finger force production task, Latash et al (2003) proposed two stages of motor learning.…”
Section: Goal-equivalent Joint Configuration Variance Increased In Rementioning
confidence: 99%
“…Most studies in adults revealed a decrease in both components of joint configuration variance (V UCM and V ORT ) with practice. However, the decrease in V UCM could be larger than (Domkin et al 2002), equal to (Domkin et al 2005), or smaller than (Kang et al 2004;Yang and Scholz 2005) the decrease in V ORT with practice. A related experiment using a slightly different approach to distinguish variance components revealed primarily decreases in V ORT in an early stage of practice, leading to a higher ratio of the two components, while V UCM decreased more than V ORT at a later stage .…”
Section: Introductionmentioning
confidence: 99%